IMPROVING THE SECOND SEMESTER STUDENTS’ READING ABILITY THROUGH THE APPLICATION OF THINK PAIR SHARE TECHNIQUE AT POLITEKNIK SEKAYU: A CLASSROOM ACTION RESEARCH - Mesi Arti; Baginda Simaibang; Magdad Hatim (ELTE Journal (English Languange Teaching and Education), 2020)
This research was aimed at finding whether the use of Think Pair Share improved the second-semester students’ reading ability at Politeknik Sekayu.Related to the purposes of the study, the research design used in this study was classroom action research. The subject of the study was the students of accounting class 2A of Politeknik Sekayu in the academic year of 2019/2020. Data collection included the application of the Think pair Share technique in three cycles. Data were analyzed using quantitatively and qualitatively. The research findings showed that the Think pair Share technique improved students’ reading comprehension. The technique enabled students to practice some reading strategies in the form of individual, pair, and team. The improvement of students’ reading ability can be seen from the result of the reading test which has the percentage score test 1 is 45%, test 2 is 64% and test 3 is 86%. This research also showed that the activities in the Think Pair Share technique enhanced students’ ability in comprehending reading. The conclusion suggested that the application of the Think Pair share technique effectively improved the second-semester students’ reading ability of Politeknik Sekayu.